Multiple treatment comparison of seven new drugs for patients with advanced malignant melanoma: a systematic review and health economic decision model in a Norwegian setting. Issue 8 (21st August 2017) - Pike, Eva; Hamidi, Vida; Saeterdal, Ingvil; Odgaard-Jensen, Jan; Klemp, Marianne
Abstract : Objective: To assess the relative effectiveness and cost-effectiveness of seven new drugs (cobimetinib, dabrafenib, ipilimumab, nivolumab, pembrolizumab, trametinib and vemurafenib) used for treatment of patients with advanced malignant melanoma in the Norwegian setting. Design: A multiple technology assessment. Patients: Patients with advanced malignant melanoma aged 18 or older. Data sources: A systematic search for randomised controlled trials in relevant bibliographic databases. Methods: We performed network meta-analyses using both direct and indirect evidence with dacarbazine as a common comparator. We ranked the different treatments in terms of their likelihood of leading to the best results for each endpoint. The cost-utility analysis was based on a probabilistic discrete-time Markov cohort model. The model calculated the costs and quality-adjusted life years (QALYs) with different treatment strategies from a healthcare perspective. Sensitivity analysis was performed by means of Monte Carlo simulation. Results: Monotherapies with a programmed cell death 1 (PD-1) immune-checkpoint-inhibitor had a higher probability of good performance for overall survival than monotherapies with ipilimumab or BRAF/MEK inhibitors. The combination treatments had all similar levels of effectiveness to the PD-1 immune-checkpoint-inhibitors. PD-1 immune-checkpoint-inhibitors are more effective and more costly compared with ipilimumab in monotherapy. Nivolumab in combination with ipilimumab had higher costs and the same level of effectiveness as the PD-1 immune-checkpoint-inhibitors in monotherapy. BRAF/MEK inhibitor combinations (dabrafenib and trametinib or vemurafenib and cobimetinib) had both similar effectiveness and cost-effectiveness; however, the combination therapies are more likely to give higher quality adjusted life year gains than BRAF or MEK inhibitor monotherapies, but to a higher cost. Conclusions: None of the drugs investigated can be considered cost-effective at what has normally been considered a reasonable willingness-to-pay (WTP) in Norway. Price reductions (from the official list prices) in the region of 63%–84% would be necessary for these drugs to be cost-effective at a WTP of €55 850 per QALY.